2018
DOI: 10.1038/s41419-018-0628-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-142-3p is downregulated in aggressive p53 mutant mouse models of pancreatic ductal adenocarcinoma by hypermethylation of its locus

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely aggressive disease with poor prognostic implications. This is partly due to a large proportion of PDACs carrying mutations in TP53, which impart gain-of-function characteristics that promote metastasis. There is evidence that microRNAs (miRNAs) may play a role in both gain-of-function TP53 mutations and metastasis, but this has not been fully explored in PDAC. Here we set out to identify miRNAs which are specifically dysregulated in metastatic PDAC. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 55 publications
(72 reference statements)
0
21
0
Order By: Relevance
“…31 Similar to tumor suppressors, dysregulation of tumor suppressor-type miRNAs by epigenetic silencing is often observed in human cancers, such as miR-142-3p, miR-142-3p, and miR-183. [32][33][34] We supposed that the upregulated miR-602 was epigenetically activated by DNA hypomethylation. Correspondingly, CpG site hypomethylation of miR-602 was observed in ESCC clinical samples, and this further verified that hypomethylation by 5-aza-CdR could dramatically augment the expression of miR-602 in ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…31 Similar to tumor suppressors, dysregulation of tumor suppressor-type miRNAs by epigenetic silencing is often observed in human cancers, such as miR-142-3p, miR-142-3p, and miR-183. [32][33][34] We supposed that the upregulated miR-602 was epigenetically activated by DNA hypomethylation. Correspondingly, CpG site hypomethylation of miR-602 was observed in ESCC clinical samples, and this further verified that hypomethylation by 5-aza-CdR could dramatically augment the expression of miR-602 in ESCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated miR-142-3p has been previously implicated in impaired hematopoiesis [20]. More recently, several studies found miR-142-3p to be hypermethylated and downregulated in aggressive metastatic cancers, including pancreatic ductal adenocarcinoma [21] and breast cancer [22], suggesting this microRNA affects cellular invasion across several cell types. Furthermore, an effect of miR-142-3p on cellular motility was seen in knockout miR-142 -/-mice, which exhibited abnormal skin wound healing upon infection [23].…”
Section: Introductionmentioning
confidence: 99%
“…The miRNA family is also significant in the anti-proliferative and pro-apoptotic processes regulated by p53 through binding cell cycle genes and proto-oncogenes 65, 66, 67, 68. In other studies, miR-142-3p, miR-155-5p, miR-518, miR-211, miR-1307, and miR-30a can all directly or indirectly stimulate the p53 signaling pathway, which shows the close relationship between miRNA and p53 69, 70, 71, 72, 73, 74…”
Section: Introductionmentioning
confidence: 81%